Multi-objective dynamic optimization of a novel suspension system for race cars - Țoțu Vlad; Alexandru Cătălin (My University, 2022)
The work approaches the dynamic optimization of an innovative suspension system (with triadbased wheel guidance mechanism) used in Formula Student race cars. The work actually continues the study from a previous paper by the authors, in which the kinematic optimization of the proposed suspension was approached. While in the case of the kinematic model, where the chassis is fixed, the optimization aimed at minimizing wheel movement-specific variations, the dynamic optimization targets the angular movements of the chassis, namely roll, pitch and yaw. The dynamic optimization process is conducted on the basis of regression models and DOE (Design of Experiments) investigation strategies, by using specific modules from the ADAMS software package (namely Insight and View).
Keywords: race car; suspension system; dynamics; optimization